Client Mobile Software Design Principles for Mobile Learning Systems - Tan, Qing; Kinshuk, Kinshuk (International Journal of Interactive Mobile Technologies (iJIM), 2009)
In a client-server mobile learning system, client mobile software must run on the mobile phone to acquire, package, and send studentâ??s interaction data via the mobile communications network to the connected mobile application server. The server will receive and process the client data in order to offer appropriate content and learning activities. To develop the mobile learning systems there are a number of very important issues that must be addressed. Mobile phones have scarce computing resources. They consist of heterogeneous devices and use various mobile operating systems, they have limitations with their user/device interaction capabilities, high data communications cost, and must provide for device mobility and portability. In this paper we propose five principles for designing Client mobile learning software. A location-based adaptive mobile learning system is presented as a proof of concept to demonstrate the applicability of these design principles.